A power management solution for Bluetooth low energy in smart homes of internet of things. (2016) - Collotta, Mario; Pau, Giovanni
The internet of things (IoT) enabled home automation to become more and more popular. A goal of IoT is to make homes smarter, also thanks to the use of wireless technologies. Bluetooth low energy (BLE) has a high potential in becoming an important technology for the IoT in low power, low cost, small devices. In fact, there is a main requirement that make a wireless protocol ideal for use in the IoT, that is the energy efficiency. To this end, this paper proposes a fuzzy-based solution that determines the sleeping time of field devices, in a home automation wireless network based on BLE, in order to improve its energy efficiency. The proposed solution determines the sleeping time of field devices according to the battery level and to the ratio of throughput to workload (Th/Wl).